Penilaian Kondisi Akustik Di Dalam Ruang Kelas Melalui Program Simulasi Odeon 5.0 (Studi Kasus: SMP Negeri 4 Banda Aceh) - Rosa Mardiana; Bastian Arifin; Izarul Machdar (Jurnal Serambi Engineering, 2018)
School is one of areas that must be controlled by noise level. In accordance with the quality standards of noise level at the school or educational institution is 55 dB. The school conditions polluted air pollution will affect the comfort and ultimately student in learning process and give bad effect for the students’ achievement concentration decreases. The aim of the research is to analyze noise level and see composite materials to reduce noise levels through computer simulation approach. Parameter acoustic test in the noisy background (Background of Noise), Sound Pressure Level Distribution, Time buzz, Speech Transmission Index (STI) and Insulation. The sample of this research is in SMPN 4 Banda Aceh. Based on the data obtained, it is found that the noise levels at the site beyond the expiry of the quality standards required that at one point in the school yard around 76.8 dB, point 2 in classrooms around 66.1 dB and point 3 outside of school grounds around 77.7 dB. Based on simulation results for Clarity / C80 superior to the material to 3, for reverberation time and decay (D50 and T30) superior to the material to 4th and 5th, while for clarity conversation / STI all the ingredients fit in either category.